UPAYA KUA DALAM MENENTUKAN MASAFATUL QASHRI BAGI WALI NIKAH YANG TIDAK ADA DITEMPAT ( Studi Kasus Di Kua Kecamatan Aek Kuasan) - Tambunan, Beny Ridho Septiansyah (Jurnal Ushuluddin, 2023)
The absence of a guardian is one of the reasons for the transfer of a person's guardianship rights. If the guardian is not in the place (ghaib) where the marriage will be held, This research method is a qualitative method with an empirical (field) approach. The data sources obtained are primary data and secondary data. As well as data collection techniques are carried out interviews, observations and documentation as supporting. The efforts of the KUA of Aek Kuasan sub-district in determining the masafatul qashri for the marriage guardian who isn’t present are canceled by the head of the KUA on the grounds that the lineage guardian from the family can be present in the marriage so that the marriage with the judge guardian that occurred was canceled with considerations in accordance with the regulations, but the implementation of this marriage still took place and was married to the lineage guardian from the woman's brother. Masafatul Qashri for the Marriage Guardian who is not present is the rejection made by the head of the KUA who follows the applicable rules. When the guardian is absent as far as the masafahqashr, then the one who marries is the local judge guardian.Keywords: KUA, Masafatul Qashri, Marriage Guardian